Against the profit motive : the salary revolution in American government, 1780-1940 - Parrillo, Nicholas R. (New Haven : Yale University Press, 2014)
In America today, a public official's lawful income consists of a salary. But until a century ago, the law frequently authorized officials to make money on a profit-seeking basis. Prosecutors won a fee for each defendatn convicted. Tax collectors received a cut of each evasion incovered. Naval officers took a reward for each ship sunk. The list goes on. This book documents the American government's 'for profit' past, to discover how profit-seeking defined officials' relationshp to the citizenry and to explain how lawmakers - by banishing the profit motive in favour of the salary - transformed that relationship forever.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 2, 2013).
Keywords: United States -- Officials and employees -- Salaries, etc. -- History; Fees, Administrative -- United States -- History; Industry; United States of America, USA; Public administration; Legal history